2001
DOI: 10.1074/jbc.m004862200
|View full text |Cite
|
Sign up to set email alerts
|

A Potential Role of Nuclear Matrix-associated Protein Kinase CK2 in Protection against Drug-induced Apoptosis in Cancer Cells

Abstract: Protein kinase CK2 (CK2) has long been implicated in the regulation of cell growth and proliferation. Its activity is generally elevated in rapidly proliferating tissues, and nuclear matrix (NM) is an important subnuclear locale of its functional signaling. In the prostate, nuclear CK2 is rapidly lost commensurate with induction of receptor-mediated apoptosis after growth stimulus withdrawal. By contrast, chemical-induced apoptosis in prostate cancer and other cells (by etoposide and diethylstilbestrol) evokes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

16
131
0
2

Year Published

2005
2005
2021
2021

Publication Types

Select...
8
2

Relationship

3
7

Authors

Journals

citations
Cited by 144 publications
(149 citation statements)
references
References 37 publications
16
131
0
2
Order By: Relevance
“…To provide a more direct confirmation of the role of CK2 as a suppressor of apoptosis we demonstrated that forced overexpression of CK2 prior to treatment of cells with etoposide or diethylstilbestrol strongly protected them against apoptosis (Guo et al, 2001). Analogous observations based on heat shock treatment of cells supported the role of CK2 in promoting cell survival Davis et al, 2002), and subsequent studies employing radiation or UV treatment of cells have made similar observations (Kato et al, 2003;Yamane and Kinsella, 2005).…”
Section: Ck2 and Cell Deathsupporting
confidence: 50%
“…To provide a more direct confirmation of the role of CK2 as a suppressor of apoptosis we demonstrated that forced overexpression of CK2 prior to treatment of cells with etoposide or diethylstilbestrol strongly protected them against apoptosis (Guo et al, 2001). Analogous observations based on heat shock treatment of cells supported the role of CK2 in promoting cell survival Davis et al, 2002), and subsequent studies employing radiation or UV treatment of cells have made similar observations (Kato et al, 2003;Yamane and Kinsella, 2005).…”
Section: Ck2 and Cell Deathsupporting
confidence: 50%
“…CK2 is a ubiquitous and constitutively active serine/ threonine protein kinase that is implicated, among many other functions, in apoptosis, 22 cell survival 23 and cell transformation. 24 The antiapoptotic action of CK2 occurs through the phosphorylation of BID, a pro-apoptotic member of the BCL-2 family, which becomes resistant to caspase cleavage 25 and the phosphorylation of ARC (apoptotic repressor with caspase recruitment domain) that blocks the activity of caspase 8.…”
Section: Discussionmentioning
confidence: 99%
“…With respect to the proposed targeting of Akt by resveratrol and EGCG (1,3,41), it may be noted that a considerable amount of information on the regulation of PTEN by CK2 exists (42,43), and, indeed, it has been reported that CK2 can directly affect the phosphorylation of Akt (44). Overexpression of CK2 has been shown to block apoptosis mediated by DNAdamaging agents as well as via death receptors, whereas the reverse seems to be the case on down-regulation of CK2 by diverse means (8,14,15,45,46). Accordingly, our observations on the actions of resveratrol and EGCG on CK2 may have strong implications regarding their cell biological effects.…”
Section: Discussionmentioning
confidence: 99%